2017
DOI: 10.1097/md.0000000000007851
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect of inflammation and metabolic syndrome on intraocular pressure

Abstract: Intraocular pressure is associated with metabolic syndrome. C-reactive protein (CRP) is associated with cardiovascular disease, irrespective of the presence of metabolic syndrome. In this study, we examined the synergistic effect of CRP and metabolic syndrome on intraocular pressure.A total of 1041 subjects were included for data analyses in this cross-sectional study. Intraocular pressure was measured using a noncontact tonometer, and serum CRP levels were measured using a commercially available kit.The intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 54 publications
(71 reference statements)
0
19
0
Order By: Relevance
“…Of these studies, 18 studies reported on the relationship between hyperlipidemia (hyperlipidemia or hypertriglyceridemia or hypercholesterolemia) and glaucoma, 7,8,32,34-39,44,45,47,48,50- 54 1 on blood highdensity lipoprotein-cholesterol (HDL-c) level and glaucoma, 55 1 on hyperlipidemia and OHT, 42 5 on blood triglyceride level and IOP, 9,10,33,43,46 2 on blood HDL-c level and IOP, 10,43 2 on total cholesterol level and IOP, 43,46 1 on low-density lipoprotein-cholesterol (LDL-C), 43 and 3 on hyperlipidemia and IOP. 40,41,49 When assessing the relationship between hyperlipidemia and glaucoma, four studies [34][35][36]39 reported on the association between both hypertriglyceridemia or hypercholesterolemia and glaucoma. We assumed that the hypercholesterolemia patients and the hypertriglyceridemia patients were the subjects of two separate studies.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these studies, 18 studies reported on the relationship between hyperlipidemia (hyperlipidemia or hypertriglyceridemia or hypercholesterolemia) and glaucoma, 7,8,32,34-39,44,45,47,48,50- 54 1 on blood highdensity lipoprotein-cholesterol (HDL-c) level and glaucoma, 55 1 on hyperlipidemia and OHT, 42 5 on blood triglyceride level and IOP, 9,10,33,43,46 2 on blood HDL-c level and IOP, 10,43 2 on total cholesterol level and IOP, 43,46 1 on low-density lipoprotein-cholesterol (LDL-C), 43 and 3 on hyperlipidemia and IOP. 40,41,49 When assessing the relationship between hyperlipidemia and glaucoma, four studies [34][35][36]39 reported on the association between both hypertriglyceridemia or hypercholesterolemia and glaucoma. We assumed that the hypercholesterolemia patients and the hypertriglyceridemia patients were the subjects of two separate studies.…”
Section: Literature Searchmentioning
confidence: 99%
“…When assessing the relationship between hyperlipidemia and IOP, one study reported on the relationship between both hypertriglyceridemia and hypercholesterolemia and IOP changes. 40 We also treated this as two studies. The detailed process of data selection is described in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%
“… 30 Mucopolysaccharides of endothelial cells were related to macrophage function and were involved in the components of the ECM. 12 The change in the ECM might lead to an increase in the resistance of the trabecular meshwork, resulting in a decrease in outflow, 31 , 32 which might induce high IOP. Our results supported the view that systemic inflammation might lead to increased IOP.…”
Section: Discussionmentioning
confidence: 99%
“… 9 11 One study had shown that systemic inflammation reflected by serum C-reactive protein levels were associated with high IOP. 12 Therefore, chronic inflammation may increase IOP. 13 It had been reported that there was a statistically significant correlation among human trabecular meshwork DNA damage, visual field damage, and IOP.…”
mentioning
confidence: 99%
“…These variables may impact pRNFL and mGCIPL measures and also co-associate with metabolic syndrome. 46 The effect size of BMI on mGCIPL thinning in this study was modest, and functional outcomes were lacking, making it uncertain whether the retinal changes were specific for MS and had clinically meaningful consequences.…”
mentioning
confidence: 86%